2019
DOI: 10.12804/revistas.urosario.edu.co/apl/a.5975
|View full text |Cite
|
Sign up to set email alerts
|

Leitura compartilhada de histórias e aprendizagem de palavras em crianças típicas e com Síndrome de Down

Abstract: La lectura compartida de historias es un recurso en la enseñanza de vocabulario en niños, pero no se sabe si ese recurso es eficaz para niños con Síndrome de Down (SD). Este estudio investigó el aprendizaje de relaciones entre palabras (sustantivo y adjetivo) y figuras, en niños con sd y con desarrollo típico (DT) a partir dela lectura repetida de una historia. Seis niños dt (3-4 años) y seis SD (5-8 años) participaron en tres sesiones individuales de lectura de un libro que contenía dospalabras desconocidas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This is broadly in keeping with parents of typically developing children (Hindman et al., 2014). Other studies have trained parents of children with Down syndrome in shared book reading techniques (van Bysterveldt et al., 2006) or used shared book reading as one of a number of approaches to support children's development of vocabulary, letter knowledge, print concepts, phonological awareness and speech articulation (Bonagamba & Schmidt, 2019; van Bysterveldt et al., 2010b). Based on a small sample and a low dose of three sessions, Bonagamba and Schmidt (2019) reported that their shared book reading procedure was not effective for teaching nouns to young children with Down syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is broadly in keeping with parents of typically developing children (Hindman et al., 2014). Other studies have trained parents of children with Down syndrome in shared book reading techniques (van Bysterveldt et al., 2006) or used shared book reading as one of a number of approaches to support children's development of vocabulary, letter knowledge, print concepts, phonological awareness and speech articulation (Bonagamba & Schmidt, 2019; van Bysterveldt et al., 2010b). Based on a small sample and a low dose of three sessions, Bonagamba and Schmidt (2019) reported that their shared book reading procedure was not effective for teaching nouns to young children with Down syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have trained parents of children with Down syndrome in shared book reading techniques (van Bysterveldt et al., 2006) or used shared book reading as one of a number of approaches to support children's development of vocabulary, letter knowledge, print concepts, phonological awareness and speech articulation (Bonagamba & Schmidt, 2019; van Bysterveldt et al., 2010b). Based on a small sample and a low dose of three sessions, Bonagamba and Schmidt (2019) reported that their shared book reading procedure was not effective for teaching nouns to young children with Down syndrome. In contrast, findings suggest that targeting parent–child interactions in shared book reading is an effective intervention approach to promote phonological awareness and letter knowledge (van Bysterveldt et al., 2006) and, when integrated with other approaches, to remediate speech error patterns (van Bysterveldt et al., 2010b).…”
Section: Introductionmentioning
confidence: 99%